2005
DOI: 10.1186/1471-2458-5-85
|View full text |Cite
|
Sign up to set email alerts
|

Health disparities and advertising content of women's magazines: a cross-sectional study

Abstract: Background: Disparities in health status among ethnic groups favor the Caucasian population in the United States on almost all major indicators. Disparities in exposure to health-related mass media messages may be among the environmental factors contributing to the racial and ethnic imbalance in health outcomes. This study evaluated whether variations exist in health-related advertisements and health promotion cues among lay magazines catering to Hispanic, African American and Caucasian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 39 publications
1
36
0
1
Order By: Relevance
“…From a clinical perspective, lack of knowledge about health disparities might contribute to the underutilization of interventions for smoking in this population. Although the media is a primary channel for public health messages, previous research has concluded that media-based health promotion efforts are lacking among outlets that target African Americans (Duerksen et al, 2005). Our sample of smokers was surprised to learn of smoking-related health disparities, yet indicated that they benefited from learning of how the consequences of smoking differentially affect African Americans.…”
Section: Discussionmentioning
confidence: 62%
“…From a clinical perspective, lack of knowledge about health disparities might contribute to the underutilization of interventions for smoking in this population. Although the media is a primary channel for public health messages, previous research has concluded that media-based health promotion efforts are lacking among outlets that target African Americans (Duerksen et al, 2005). Our sample of smokers was surprised to learn of smoking-related health disparities, yet indicated that they benefited from learning of how the consequences of smoking differentially affect African Americans.…”
Section: Discussionmentioning
confidence: 62%
“…Commonly, the disparities in health status associated with ethnic group membership are preceded by ethnic differences in health information (Duerksen et al 2005). Consistent with the health belief model (Becker 1974) and diffusion theory (Rogers 2003), messages in media can stimulate attention or offer cues to action that either promote or inhibit health behaviours.…”
Section: Background: Ethnicity and Disparities In Prenatal Care Utilimentioning
confidence: 81%
“…Although a few studies have documented the impact of messages in the media with women, 8,20 this is the first published study to examine messages in the media specifically about infant sleep environment. We found that, 16 years after the initial AAP recommendations to place infants in a nonprone position, 11 more than one third of pictures of sleeping infants in magazines geared toward childbearing women demonstrated infants in an inappropriate sleep position and two thirds of pictures of the infant sleep environment were not consistent with AAP recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…6 Advertisements and other messages in the media can influence individuals' perceptions of personal risk and strategies to reduce risk. 8 For example, coverage in the media increases mammogram use for women who do not have regular contact with or access to a physician. 9 The rate of sudden infant death syndrome (SIDS) decreased from 1.2 deaths per 1000 live births in 1992, 10 when the American Academy of Pediatrics (AAP) first published guidelines regarding infant sleep position, 11 to 0.57 deaths per 1000 live births in 2001.…”
mentioning
confidence: 99%